Pemberdayaan Masyarakat Melalui Program Pelatihan Pembuatan Spray Anti Nyamuk Berbahan Serai di Desa Kolam Kecamatan Percut Sei Tuan - Nabila Maharani; Mutiara Simanungkalit; Rutpani Suryani; Desi Sarina; Fitri Salsabila; Siti Rahmadani; Tamara Adisa Aprilia; Carissa Mumtaza; Arum Dwi Saputri; Adinda Syafira; Fauzi Kurniawan; Tegar Anggi Handika (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This activity aims to analyze the effectiveness of a community empowerment program through training on making mosquito repellent spray using lemongrass in increasing the knowledge and skills of residents in Kolam Village. The main issues addressed are the abundant availability of lemongrass that has not been economically utilized and the high dependence of the community on chemically-based mosquito repellents. The method used is a training-based empowerment program with the active participation of 15 housewives, which includes stages of socialization, demonstration, and independent practice based on experiential learning. The results of the activity showed a significant increase in the participants' knowledge level from 40% to 80%. In addition, participants successfully mastered practical skills in producing mosquito repellent spray independently. The conclusion of this activity is that systematically and participatively conducted training is proven effective in optimizing local potential